Peningkatan Pengetahuan Jajanan Sehat melalui Penyuluhan dan Demonstrasi Deteksi Bahan Kimia Berbahaya Makanan pada Anak Usia Sekolah: Increasing Knowledge of Healthy Snacks through Counseling and Demonstration of Detection of Food Harmful Chemicals in School-Age Children - Rahman, Adam Aulia; Jannah, Nanda Raudhatil; Setyaningrum, Dwi Larasati; Firdaus, Wahyu Alfath; Husnaini, Rovi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The use of harmful food chemicals in snacks for schoolchildren remains a widespread issue. Each year, BPOM (the Indonesian Food and Drug Authority) identifies the presence of formaldehyde, borax, and food additives that exceed permissible levels in snack foods. School snacks are essential as they provide energy and vital nutrients for children. However, unhealthy snacks containing dangerous chemicals can impede optimal growth and development, potentially leading to various health issues. This community service, funded by an internal grant from Universitas Muhammadiyah Bandung, aims to educate children about healthy snacks through outreach activities and detecting harmful food chemicals. Pretest and posttest data were collected from 43 children from elementary to junior high school in RW 02 Cipadung Kidul, Panyileukan, Bandung. The results indicate a significant increase in the children's understanding of healthy snacks and harmful food chemicals. Initially, they answered an average of 44.76% of questions correctly. After participating in the program, this number rose to 93.81%. This increase in knowledge indicates that educational outreach, combined with demonstrations on detecting harmful food chemicals, effectively engages children and enhances their understanding of the material presented.